2017
DOI: 10.18203/2320-1770.ijrcog20174407
|View full text |Cite
|
Sign up to set email alerts
|

A study of N-acetyl cysteine, metformin and vitamin D3 with calcium on clinical and metabolic profile in PCOS

Abstract: Background: Polycystic ovarian syndrome (PCOS) is characterized by the combination of hyperandrogenism, chronic anovulation and polycystic ovaries. Objective of present study was to compare the effects of N-acetyl cysteine, metformin and vitamin D3 with calcium on clinical and metabolic profile in PCOS.Methods: 66 women were randomly assigned into three equal treatment groups. Group 1 received N-acetyl cysteine, 600 mg three times a day. Group 2 metformin hydrochloride, 500 mg two times a day for 1 week, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…Regarding its insulin-sensitizing effects, N-acetylcysteine has been found to decrease FG, FI, and the FG/FI ratio after 3 months of treatment, 14 consistent with the present study. In another study, the effects of N-acetylcysteine on FG, FI, FG/FI, and HOMA index were better or equal to those of metformin.…”
Section: R E T R a C T E Dsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding its insulin-sensitizing effects, N-acetylcysteine has been found to decrease FG, FI, and the FG/FI ratio after 3 months of treatment, 14 consistent with the present study. In another study, the effects of N-acetylcysteine on FG, FI, FG/FI, and HOMA index were better or equal to those of metformin.…”
Section: R E T R a C T E Dsupporting
confidence: 93%
“…To our knowledge, the present study is the first to compare the reproductive and metabolic effects of N ‐acetylcysteine and l ‐carnitine therapy for women with PCOS. Neither of the drugs reduced BMI, although previous trials reported a significant reduction in BMI after both N ‐acetylcysteine and l ‐carnitine therapy. Variations in pretreatment BMI, drug doses, associated lifestyle changes, and the study populations might explain these different effects on BMI.…”
Section: Discussionmentioning
confidence: 76%
“…Subgroup analyses based on follow-up time showed that longer duration of NAC intervention was associated with more effective changes in BMI, FBG and FI, and longer duration of NAC treatment was associated with better outcomes. This is consistent with the conclusions of the two included studies (28,29). PCOS is a common condition with important effects throughout the life cycle, including reproductive, metabolic, and psychological effects, so long-term interventions are important in PCOS management (39).…”
Section: Figuresupporting
confidence: 88%
“…Overall, we included 11 RCTs involving 869 women with PCOS, published between 2009 and 2022 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Of these studies, the majority were conducted in Asia and only 1 was conducted in Africa (30), of which 5 were conducted in India (25,26,28,29,32), 4 in Iran (22,24,27,31), 1 in Egypt (30), and 1 in Turkey (23).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation